Performance of high-temperature thermosetting polyimide composites modified with thermoplastic polyimide. (October 2020) - Ke, Hongjun; Zhao, Liwei; Zhang, Xiaohong; Qiao, Yingjie; Wang, Guoyong; Wang, Xiaodong
Abstract: The preparation of polyimide (PI) resin with high heat resistance and toughness is a significant challenge. In this study, thermoplastic PI (TPI) was used to toughen thermosetting PIs, and toughened PI (TPI/PI) blends were prepared. The modified PI resin system exhibited good thermal stability, excellent heat resistance, and high toughness. The results indicated that the TPI/PI blends maintained the curing behavior and characteristics of the PI oligomer. The Tg of the cured TPI/PI blend exceeded 395 °C, and the T 5% values were in the range of 533–563 °C, suggesting excellent thermal stability and heat resistance. The maximum impact strength was increased by 46% compared with that of pure PI, indicating the excellent toughening effect of the TPI. Carbon fiber-reinforced PI composites were prepared using the toughening system as a matrix. The compression-after-impact values of the carbon fiber-reinforced PI composites were up to 190 MPa, indicating the excellent toughness of the materials. Highlights: Thermoplastic polyimide (TPI) was used to toughen thermosetting polyimide (PI), and a toughened PI blend was prepared. The toughened PI resin system exhibited good thermal stability, good heat resistance, and high toughness. A carbon fiber-reinforced PI composite was prepared by using the toughened PI resin systemas a matrix. The CAI (compression-after-impact) value of the carbon fiber-reinforced PI composite with 10% TPI could reach 190 Mpa.